Hubungan Dukungan Sosial dan Kepatuhan Terapi ARV dengan Tingkat Depresi pada ODHA di Kota Kupang - Steven Simplisius Elim (Universitas Nusa Cendana, 2026)
Introduction : Depression consistently tends to be experienced by people living with HIV/AIDS (PLWHA) at a rate of two to four times higher than the normal population. Two factors are social support and poor therapy compliance. Objectives: To analyse the relationship between social support and ARV therapy adherence with the level of depression in PLWHA in Kupang. Methods: This study employed an observational analytical research design with a cross-sectional approach involving PLWHA. Data were collected using the Hamilton Depression Rating Scale (HDRS), Oslo Social Support Scale (OSSS-3), and The Medication Adherence Rating Scale (MARS-5) questionnaires. Sampling was conducted using a non-probability snowball sampling technique, resulting in a total of 98 respondents. This study was analysed univariately and bivariately using the Somer's D test. Results: The bivariate analysis results between social support and depression level had a p-value of 0.006 (p<0.05). The bivariate analysis results between ARV therapy adherence level and the level of depression had a p-value of 0.097 (p>0.05). Conclusion: Social support significantly affects depression levels in PLWHA in Kupang, while ARV therapy adherence shows no significant relationship with their depression levels. Keywords: Social Support, ARV Therapy Adherence, Depression